Praktik Income Smoothing: Studi Empiris Pada Perusahaan Manufaktur Di Indonesia - Ratu Vera Safira; Kodriyah; Nikke Yusnita Mahardini (Universitas Serang Raya, 2022)
This study aims to determine the effect of net profit margin, dividend payout ratio and bonus plan on income smoothing partially at manufacturing companies listed on Indonesia Stock Exchange period 2014-2019. The method used is quantitative with associative (causality) design. The study population numbered 182 companies with purposive sampling method and taken samples of 21 companies in period 2014-2019, so that observation data is 126 also analyzed by SPSS version 25. This data is in the form of annual financial statements from the official website of Indonesia Stock Exchange www.idx.co.id and official website of companies. The data analysis technique is descriptive statistical analysis and logistic regression analysis. Based on the study result, can be conclude that: 1) there is not a significant effect between profit margin and income smoothing, 2) there is a significant effect between dividend payout ratio and income smoothing, 3) there is a significant effect between bonus plan and income smoothing.